Ethnic Identity of the Mountain Jews and Indicators of Its Reproduction - Shakhbanova, Madina M. (Journal of History Culture and Art Research, 2018)
This article considers the indicators and mechanisms for the reproduction of the ethnic identity of Mountain Jews. Cognitive, emotional and behavioral aspects of their ethnic identity were shown based on the empirical study. It is established that the national (native) language, ethnic traditions, religion, common life in a certain territory, common character and similar behavior, national literature, historical homeland and historical memory are the most important markers for the reproduction of the ethnic identity of Mountain Jews. The national language has a leading position in this hierarchy. The level of possession of among the surveyed Mountain Jews is not at a high level. Self-awareness is the most important parameter of determining the ethnicity of a person for Mountain Jews through which identification with a specific ethnic community takes place. Moreover, the awareness of belonging to one's own people consists in knowing their national (native) language, traditions, customs, ethnocultural specifics, belonging to their ethnic group.